Study Protocol: Transition_psy a Multicenter Prospective Longitudinal Cohort Study Assessing Risk and Protective Factors to Develop Psychopathology in Transitional Age Youth in Belgium - Reis, Joana; Marchini, Simone; De Leeuw, Anthony; Slama, Hichem; Leys, Christophe; Delhaye, Marie; Kornreich, Charles; Nicolis, Hélène; Delvenne, Véronique (Frontiers in Psychiatry, 2021)
Introduction: Emerging adults are a particularly at-risk population in mental health. The primary aim of the Transition_psy study is to evaluate changes in mental health care need and quality of life during transition from Child and Adolescent Mental Health Services (CAMHS) to Adult Mental Health Services (AMHS). The relationship between these changes and genetic or environmental vulnerabilities and clinical dimensions representing risk and protective factors to the development of psychopathology will be analyzed. We also aim to explore how each factor plays, specifically, a role in developing internalizing and externalizing symptoms, in order to predict the most common paths of psychopathology in transitional age youth (TAY). Methods and Analysis: Transition_psy is a multicenter prospective longitudinal cohort study. The transversal and trans-diagnostic approach consists of a dimensional evaluation: 300 youth at the age of 17 will be included in a cohort of in-patients, out-patients and control group. Participants will be assessed at baseline (T0) and 24 months later (T1). The primary objective to determine changes in self-rated Health Of The Nation Outcome Scales For Children And Adolescents (HONOSCA-SR) and WHO Quality of Life-BREF (WHOQOL-BREF) scores between T0 and T1. Pearson correlation and mediation analysis will be performed. A secondary objective analysis using mediation and moderation models with several dimensional aspects, including self-reported and cognitive measures, will be conducted to disentangle the potential relationships between the two scores. Discussion: Transition from CAMHS to AMHS occurs at a crucial age in terms of the continuum between adolescent and adulthood psychopathology. This collaborative and cohesive protocol between CAMHS and AMHS represents the first national cohort study about Transition Psychiatry in French-speaking Belgium. Ethics and Dissemination: The study protocol was approved by the Institutional Review Boards (IRB) of the three participating sites. Results will be published in peer-reviewed journals and disseminated at national and international conferences. This trial was registered in ClinicalTrials.gov (Identifier: NCT04333797) on 3 April 2020.